2016
DOI: 10.3892/ol.2016.4868
|View full text |Cite
|
Sign up to set email alerts
|

APC promoter is frequently methylated in pancreatic juice of patients with pancreatic carcinomas or periampullary tumors

Abstract: Abstract. Early detection of pancreatic and periampullary neoplasms is critical to improve their clinical outcome. The present authors previously demonstrated that DNA hypermethylation of adenomatous polyposis coli (APC), histamine receptor H2 (HRH2), cadherin 13 (CDH13), secreted protein acidic and cysteine rich (SPARC) and engrailed-1 (EN-1) promoters is frequently detected in pancreatic tumor cells. The aim of the present study was to assess their prevalence in pancreatic juice of carcinomas of the pancreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Genetic analysis of pancreatic juice of the patients with pancreatic cancer was able to detect mutant DNA, such as Kras , TP53 , and SMAD4 , for the discrimination of pancreatic cancer from the healthy controls or pre‐cancerous lesions [ 105 , 106 ]. Additionally, promoters of adenomatous polyposis coli ( APC ) and histamine receptor H2 ( HRH2 ) genes were found to be frequently methylated in pancreatic cancer juice, serving as potential diagnostic biomarkers [ 107 ]. Through the detection of exosome‐derived miRNAs from pancreatic juice, Japanese researchers found that miR‐21 and miR‐155 levels could discriminate PDAC patients from chronic pancreatitis patients with an AUC of 0.90 and 0.89, respectively, and that a combination with cytology displayed even higher accuracy [ 108 ].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Genetic analysis of pancreatic juice of the patients with pancreatic cancer was able to detect mutant DNA, such as Kras , TP53 , and SMAD4 , for the discrimination of pancreatic cancer from the healthy controls or pre‐cancerous lesions [ 105 , 106 ]. Additionally, promoters of adenomatous polyposis coli ( APC ) and histamine receptor H2 ( HRH2 ) genes were found to be frequently methylated in pancreatic cancer juice, serving as potential diagnostic biomarkers [ 107 ]. Through the detection of exosome‐derived miRNAs from pancreatic juice, Japanese researchers found that miR‐21 and miR‐155 levels could discriminate PDAC patients from chronic pancreatitis patients with an AUC of 0.90 and 0.89, respectively, and that a combination with cytology displayed even higher accuracy [ 108 ].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Importantly, the study demonstrating the lowest sensitivity utilised DNA sequencing technology to detect KRAS mutation [ 42 ] and it is well recognised that this technique has a lower sensitivity than methods such as RFLP [ 47 ]. A second study demonstrating low sensitivity was that of Trumper et al [ 42 ]; one of the few prospective studies identified.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that some Wnt ligands cannot activate b-Catenin, and so act as Wnt/b-Catenin antagonists, examples of which include WNT5a and WNT7a, both of which are commonly silenced in CRC, pancreatic and lung cancer [55,56]. APC is frequently mutated in CRC, but it is also inactivated by promoter hypermethylation in colon, breast and pancreatic cancer [57][58][59]. NKD2, DACT2 and CXXC4 inhibit DSH.…”
Section: Aberrant Divisionmentioning
confidence: 99%